State support of the livestock industry in the Republic of Kazakhstan: trends and results (Journal of Economic Research & Business Administration, 2017)
The paper discusses the main directions of state support of the livestock industry in the Republic ofKazakhstan. Studied the main government programs implemented in the country in the livestock industry.Consider measures aimed at improving the competitiveness of the industry. Studied internationalexperience of support to agriculture in developed countries (USA, Canada, UK, Germany, Australia).The analysis of the implementation of the state program “Development of export potential of cattle meatin 2011-2015”. The data on the availability of projects implemented under the program in the Akmolaregion. We analyzed the livestock industry of credit and subsidy processes through subsidiaries of JSC“NMH KazAgro” in 2015. The directions and the size of livestock subsidies. The necessity of state supportof agricultural producers in order to increase the competitiveness of livestock production.